2022
DOI: 10.1590/s2179-975x9820
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of Eigenmannia desantanai (Gymnotiformes: Sternopygidae) in southern Pantanal, Brazil

Abstract: Aim This study investigated changes in the dietary composition and trophic niche breadth of Eigenmannia desantanai in the context of hydrological periods, rivers, and ontogeny. Methods Collections were performed monthly on the Paraguay and Amonguijá Rivers between February 2009 and January 2011. Results A total of 338 specimens of E. desantanai were collected, 224 of which came from the Amonguijá River and 114 from the Paraguay River. In all, 21 food items were identified. Fully remains of digested animals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Nevertheless, the surface fish Eigenmannia trilineata and other species of Eigenmannia have been observed to be nocturnal (Tan et al, 2005). Eigenmannia hide in roots, rocks, and leaf litter during the day and actively forage at night (Hopkins, 1974;Hopkins, 1981;Deng and Tseng, 2000;Tan et al, 2005;Stamper et al, 2010;Fortune et al, 2020;Gouveia et al, 2022) We traveled to the São Vicente II cave and measured the electrosensory and locomotor behavior of both surface Eigenmannia trilineata and cave Eigenmannia vicentespelaea (Fortune et al, 2020). We used a custom array of amplified electrodes, 50cm spacing, that both captured the electric behavior of nearby fish, and allowed us to calculate the positions of these fish (Madhav et al, 2018).…”
Section: Weakly Electric Cavefishmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the surface fish Eigenmannia trilineata and other species of Eigenmannia have been observed to be nocturnal (Tan et al, 2005). Eigenmannia hide in roots, rocks, and leaf litter during the day and actively forage at night (Hopkins, 1974;Hopkins, 1981;Deng and Tseng, 2000;Tan et al, 2005;Stamper et al, 2010;Fortune et al, 2020;Gouveia et al, 2022) We traveled to the São Vicente II cave and measured the electrosensory and locomotor behavior of both surface Eigenmannia trilineata and cave Eigenmannia vicentespelaea (Fortune et al, 2020). We used a custom array of amplified electrodes, 50cm spacing, that both captured the electric behavior of nearby fish, and allowed us to calculate the positions of these fish (Madhav et al, 2018).…”
Section: Weakly Electric Cavefishmentioning
confidence: 99%
“…The amplitudes of electric fields increase with the size of fish (Hopkins et al, 1990;Curtis and Stoddard, 2003;Gavassa et al, 2012) and can be used as a nonvisual proxy to estimate body size. However, Gavassa et al (2013) have shown that social interactions can drive significant changes in the amplitude of electric fields. Further, hormones can increase the amplitudes of electric fields (Markham et al, 2009a;Migliaro and Silva, 2016).…”
Section: Amplitudes Of Electric Fieldsmentioning
confidence: 99%
“…In dynamic and productive environments, such as those found in tropical regions, hydrological variations driven by the seasonality of floods and the resultant connectivity of environments can change the availability and variety of food items (Lowe-McConnell, 1999;Scanferla & Súarez, 2016;Gouveia et al, 2022). During floods, river flow increases, connecting aquatic and terrestrial habitats.…”
Section: Introductionmentioning
confidence: 99%